Westonci.ca is the premier destination for reliable answers to your questions, brought to you by a community of experts. Get quick and reliable solutions to your questions from knowledgeable professionals on our comprehensive Q&A platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.

ollow the steps to solve this equation.

3(2x + 6) – 4x = 2(5x – 2) + 6

1. Use the distributive property: 6x + 18 – 4x = 10x – 4 + 6

2. Combine like terms: 2x + 18 = 10x + 2

3. Use the subtraction property of equality: 18 = 8x + 2

4. Use the subtraction property of equality: 16 = 8x

5. Use the division property of equality:


Sagot :

Answer:

x = 2, because 16/8 = (8x)/8

Step-by-step explanation:

Devide both sides by the coefficient of variable